Evolution of a self-assembled chessboard nanostructure spinel in a CoFeGaMnZn multicomponent oxide. Issue 12 (18th June 2022) - Pal, Avnish Singh; Lal Das, Aman Kumar; Singh, Ankit; Knowles, Kevin M.; Ahmad, Md. Imteyaz; Basu, Joysurya
ABSTRACT: Mixed oxides of CoFeMn, ZnGaMn and CoFeGaMnZn have been pelletised, sintered at 1250°C for 24 hours, and then quenched and aged at 375°C for 150 hours to determine their phase compositions and microstructure evolution. After sintering and ageing, chessboard nanodomains of CoFe2 O4 and CoMn2 O4, and ZnGa2 O4 and ZnMn2 O4 spinel phases evolve in the CoFeMn and ZnGaMn oxides, respectively. In the CoFeGaMnZn multicomponent oxide, chessboard nanodomains of similar phases are also observed after sintering and ageing. These spinel phases are all likely to have mixed chemistry, and this often causes polymorphic transformations from spinel crystal structures with cubic F Bravais lattices (FCC) to ones with tetragonal I (BCT) Bravais lattices, often described in the literature in terms of crystal structures with tetragonal F (FCT) Bravais lattices. The nanodomains have specific orientation relationships with respect to one another, with {220} planes as their boundary planes with respect to a FCT unit cell description. The nanodomain size in the multicomponent oxide is significantly smaller than in the ternary mixed oxides because of the slower diffusion kinetics in this multicomponent oxide.